Magyar futballtársaságok szervezeti kérdései - Bácsné Bába Éva (2017)
This article has been written to present business-based functioning of Hungarian soccer clubs by structural analysis. The national first-league (NB I) clubs operate in the legal form of for-profit enterprises, that shows their business-type operation. My goal is to assess what kind of organizational solutions characterize the soccer clubs in the national league. I analyze organizational structure of clubs from aspects of legal form, ownership structure and division of labor in the organizaton. I would like to find out whether process of structural transformation that is directed at the realization of the appropriate form of enterprise and the structural setup was succesfull, and could combine economic and sports successes, or not. And whether in Hungary business-based sports models are efficiently operable, or not.